Lithium Ion Batteries Fabricated with Ionic Ladder-Like Polysilsesquioxane Hybrid Ionogels - Lee, Jin Hong; Lee, Albert S.; Hong, Soon Man; Hwang, Seung Sang; Koo, Chong Min (AMER SCIENTIFIC PUBLISHERS, 2017)
A new cross-linkable ionic group-functionalized ladder-like structured polysilsesquioxane was utilized as crosslinker for fabrication of hybrid ionogels. The ionic ladder-like polysilsesquioxane was completely solution processable in ionic liquid electrolytes and through chemical crosslinking, hybrid ionogel electrolytes with high ionic conductivity and electrochemical stability were obtained. Lithium ion batteries assembled with these hybrid ionogels electrolytes exhibited excellent cell cycling performance at elevated temperatures, suggesting the highly utile nature of our hybrid ionogel electrolytes.
Keywords: THERMOPLASTIC POLYSILSESQUIOXANES; ELECTROLYTES